Formation of Linguistic Competencies in Teaching Paronymous Words Given in Mother Language and Reading Literacy Textbook (Texas Journal of Philology, Culture and History, 2023)
Enriching the vocabulary of elementary school students with paronyms practical issues of formation of speech competences the issues of appropriate use of paronymous words in the speech process are covered.